If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7k + 6(1 + 8k) = 0 7k + (1 * 6 + 8k * 6) = 0 7k + (6 + 48k) = 0 Reorder the terms: 6 + 7k + 48k = 0 Combine like terms: 7k + 48k = 55k 6 + 55k = 0 Solving 6 + 55k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 55k = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 55k = 0 + -6 55k = 0 + -6 Combine like terms: 0 + -6 = -6 55k = -6 Divide each side by '55'. k = -0.1090909091 Simplifying k = -0.1090909091
| -3s=-12 | | 8+2ln(3x-8)=22 | | y-(-3)=6 | | 3x-3+2x-4=6 | | -6=4x-1 | | 3(-32+25)+7= | | 5x-6+90=3x | | 7(g+4)=49 | | 5xsquare+4=136 | | -14+11=m-2 | | -4x-5(-x+4)=-31 | | 2+7(18+10)= | | 3x+5x-6+90= | | 6m+5=m | | 5x^2-7x+39=0 | | 42-6=6(z+2)+8 | | 5(k+10)=55 | | 37-g=4g | | -8=6-n | | z-z+1+10z= | | 5x+178=3x+152 | | 1.5c_2.4=6 | | 54=6x+3(-7x-12) | | 0.19+0.03(y+2000)=1160 | | 2=35 | | 6n+13-2n=-15 | | 5(x+7)-3x=11 | | -6(-8x+16)=144 | | y-.8=1.4(x-1) | | q-16=2 | | -5x-2(-2x+14)=-34 | | z-z+1+10= |